PEMBERDAYAAN WANITA SEBAGAI TIM KELOMPOK PENDUKUNG (KEKEP) IBU NIFAS DALAM MENJAGA KENYAMANAN IBU SELAMA MASA NIFAS - Harahap, Juraida Roito; Helina, Siska; Daiyah, Isrowiyatun (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2022)
Postpartum mothers need real experience, one of which is being given support from support groups such as psychological support and also physical support that must also be met. This support group can come from the community who are in the community itself. In the area of ​​the Independent Practice Midwife Siti Juleha A.Md.Keb there are still cases of perineal sutures that re-open at 1 week postpartum in patients with poor personal hygiene and are not allowed to consume protein, 1 patient had never breastfed her baby for 1 week after delivery with the reason of being tired and wanting to rest. The purpose of this community service dedication (Pengabmas) is to form a Support Group Class team (KEKEP) for postpartum mothers. Community service activities were carried out in November 2016, at PMB Siti Juleha. The method of activity is question and answer lectures, brain storming, demonstrations and demonstrations. The materials used are leaflets, flipcharts, phantoms (props), mattresses, modules, postpartum pocket books and information sheet books. The results obtained were the formation of a postpartum women's KEKEP team consisting of 12 women. The most common problems during the puerperium are not good at breastfeeding, the most sources of information are parents and local residents, there is an increase in knowledge about the postpartum period and skills in breastfeeding techniques, breast care, breast exercise and baby massage. It is recommended for monitoring and evaluation (monev) of the role of KEKEP for postpartum mothers. Keywords: Empowerment, Woman, Postpartum, KEKEP